2014
DOI: 10.7860/jcdr/2014/8387.4268
|View full text |Cite
|
Sign up to set email alerts
|

Low Hemoglobin Level a Risk Factor for Acute Lower Respiratory Tract Infections (ALRTI) in Children

Abstract: Background: Acute lower respiratory tract infection is a major cause of death in under five years of age, and anemia is the commonest co-factor in pediatric patients seeking medical advice especially in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
58
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 14 publications
4
58
0
2
Order By: Relevance
“…Male preponderance was found (59.8%) with male to female ratio 1.5:1. Similar results were found in different studies, 70.7% in Malla T et al [1] , 57.3% in Hussain SQ et al [17] , 63% in Ramakrishnan K et al [20] and 64.42% in Savitha MR et al [21] . The gender wise discrimination of the children continues even before birth and continues throughout the life, and utilization of health care services is another example of this continued discrimination as evident by less number of female in the above studies.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Male preponderance was found (59.8%) with male to female ratio 1.5:1. Similar results were found in different studies, 70.7% in Malla T et al [1] , 57.3% in Hussain SQ et al [17] , 63% in Ramakrishnan K et al [20] and 64.42% in Savitha MR et al [21] . The gender wise discrimination of the children continues even before birth and continues throughout the life, and utilization of health care services is another example of this continued discrimination as evident by less number of female in the above studies.…”
Section: Discussionsupporting
confidence: 89%
“…72 out of 82 (87.8%) were between 6-24 months. Fifty cases (60.9%) were infants from 6 months to 1 year of age and 22 children (26.8%) belonged to age group 13-24 months, which is quite comparable to studies conducted by Malla T et al [1] , Hussain SQ et al [17] and Rijal P et al [18] . This signifies that ALRTI is most common in age group of <1 year.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Several studies have identified very low Hb levels as a risk factor for lower respiratory tract infections; however, those studies were carried out in children; therefore, the conclusions cannot be generalized to the general population or to blood donors . None of the studies accounted for comorbidity.…”
Section: Discussionmentioning
confidence: 99%